2018
DOI: 10.1021/acs.molpharmaceut.8b00047
|View full text |Cite
|
Sign up to set email alerts
|

Fluorouracil-Loaded Gold Nanoparticles for the Treatment of Skin Cancer: Development, in Vitro Characterization, and in Vivo Evaluation in a Mouse Skin Cancer Xenograft Model

Abstract: Fluorouracil (5-FU) is an antimetabolite drug used in the treatment of various malignancies, such as colon and skin cancers. However, its systemic administration results in severe side effects. Topical 5-FU delivery for the treatment of skin cancer could circumvent these shortcomings, but it is limited by the drug poor permeability through the skin. To enhance 5-FU efficacy against skin cancer and reduce its systemic side effects, it was loaded into a gold nanoparticle (GNP)-based topical delivery system. 5-FU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 72 publications
(129 reference statements)
0
58
0
1
Order By: Relevance
“…Recently, Safwat et al reported that 5FU-loaded cetyltrimethyl ammonium bromide (CTAB)-coated AuNPs (5FU/ CTAB-AuNPs) exhibited in vitro drug release only up to 24 hours and that incorporation of 5FU/CTAB-AuNPs into Pluronic F127 gel sustained the rate of drug release. 27 Safwat et al also reported that 5FU-loaded TGA-capped AuNPs and glutathione-capped AuNPs exhibited pH-responsive in vitro drug release profiles, although drug release was completed within 12 hours. 12 In addition, Duan et al reported that 5FUloaded poly(lactic acid-4-hydroxyproline-polyethylene glycol) NPs showed an initial burst release of 5FU (~60%) up to 24 hours, followed by sustained 5FU release .90 hours.…”
Section: In Vitro Drug Release Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Safwat et al reported that 5FU-loaded cetyltrimethyl ammonium bromide (CTAB)-coated AuNPs (5FU/ CTAB-AuNPs) exhibited in vitro drug release only up to 24 hours and that incorporation of 5FU/CTAB-AuNPs into Pluronic F127 gel sustained the rate of drug release. 27 Safwat et al also reported that 5FU-loaded TGA-capped AuNPs and glutathione-capped AuNPs exhibited pH-responsive in vitro drug release profiles, although drug release was completed within 12 hours. 12 In addition, Duan et al reported that 5FUloaded poly(lactic acid-4-hydroxyproline-polyethylene glycol) NPs showed an initial burst release of 5FU (~60%) up to 24 hours, followed by sustained 5FU release .90 hours.…”
Section: In Vitro Drug Release Profilementioning
confidence: 99%
“…The drug-loaded FA-polymer-AuNPs nanoconjugates (5 mg) were dispersed in 2 mL of PBS (pH 7.4), packed in a dialysis bag (MWCO=2,000) and immersed in PBS (25 mL) at 37°C under magnetic stirring. 27 The amount of drug released at different time intervals in the release medium was determined by reverse phase HPLC technique. All the experiments were carried out in triplicates and the average cumulative percentage of drug release was plotted against time.…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…The better SP permeability, flux, and skin deposition observed for the LeciPlex gel might be attributed to several factors. Cationic surface charge of LeciPlex facilitates their interaction with the negatively charged cell surface, which in turn leads to better drug uptake and permeation through the skin [64][65][66]. Further, the small particle size of the LeciPlexes is another important factor that contributes to their enhanced skin permeation.…”
Section: Ex Vivo Skin Permeation Studiesmentioning
confidence: 99%
“…Because gold and silver nanoparticles may also be used as vehicles for delivery of, for example, psoriasis therapy and chemotherapy , we suggest that future treatment trials would benefit from using OCT and CM imaging to track nanoparticles that have contrast agent properties in vivo.…”
Section: Discussionmentioning
confidence: 99%